1996
DOI: 10.1038/bjc.1996.320
|View full text |Cite
|
Sign up to set email alerts
|

Lack of prognostic significance of epidermal growth factor receptor and the oncoprotein p185HER-2 in patients with systemically untreated non-small-cell lung cancer: an immunohistochemical study on cryosections

Abstract: Summary The prognostic role of the epidermal growth factor receptor (EGFR) and the related receptor p185HER-2 in lung cancer is as yet undefined. We investigated the immunohistochemical expression of EGFR (monoclonal antibody RI; Amersham) and pl85HER-2 (polyclonal antibody A485; Dako) in cryosections. A total of 186 unselected and systemically untreated patients with non-small-cell lung cancer (NSCLC) diagnosed and treated at Odense University Hospital, Denmark, were included. Median follow-up period was 66 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 29 publications
3
51
1
1
Order By: Relevance
“…Careful review of the data presented by Kern et al (1990) reveals that their stage IIIA patients had a better prognosis than the patients in stage II and that the pN-category was not of significant prognostic importance (P = 0.95). Pfeiffer et al (1996) did not report differences in survival in AC overexpressing p185 however, the staining frequency in AC was only 26%. In our study, p185 overexpression is of significant prognostic importance for AC histology (P < 0.01) by univariate analysis but not of independent prognostic importance by multivariate analysis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Careful review of the data presented by Kern et al (1990) reveals that their stage IIIA patients had a better prognosis than the patients in stage II and that the pN-category was not of significant prognostic importance (P = 0.95). Pfeiffer et al (1996) did not report differences in survival in AC overexpressing p185 however, the staining frequency in AC was only 26%. In our study, p185 overexpression is of significant prognostic importance for AC histology (P < 0.01) by univariate analysis but not of independent prognostic importance by multivariate analysis.…”
Section: Discussionmentioning
confidence: 80%
“…Overerexpression of p185 were reported in 28-80% AC (Kern et al, 1990;Bongiorno et al, 1994;Tateishi et al, 1991;Shi et al, 1992;Pfeiffer et al, 1996), 2-45% SCC (Kern et al, 1990;Pfeiffer et al, 1996;Shi et al, 1992;Tateishi, 1992;Volm et al, 1992) and 0-20% LC (Kern et al, 1990;Pfeiffer et al, 1996). Some of these studies used paraffin embedded slides (Kern et al, 1990;Tateishi, 1992;Volm et al, 1992) or applied p185 antiserum (Kern et al, 1990;Tateishi et al, 1991;Pfeiffer et al, 1996) for immunohistochemistry. Chiu et al (1994) could convincingly demonstrate in a controlled comparative analysis of paraffin-embedded slides and cryostat sections that rates of p185 overexpression were approximately doubled in cryostat sections.…”
Section: Discussionmentioning
confidence: 99%
“…Another unsolved problem is the association between HER2 status and prognosis in lung cancer patients. Overexpression of the HER2 protein is associated with shorter survival in some, 1,5,16 but not all, 4,6,17,18 reports. Overexpression of p185 HER2 was evaluated by IHC in those studies.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6] This oncogene family encodes for the growth factor tyrosine kinase receptors, which activate the intracellular signal-transduction pathway for cell proliferation. The product of the HER2 (erbB2) gene is a 185 dalton transmembrane protein (p185 HER2 ) tyrosine kinase.…”
mentioning
confidence: 99%
“…Immunohistochemical studies have reported EGFR overexpression in 22 -81% of NSCLC tumours depending on the antibody used and cut point that defines overexpression (Veale et al, 1987;Volm et al, 1993;Pfeiffer et al, 1996;Cornianu and Tudose, 1997;Pastorino et al, 1997;Rusch et al, 1997;Fontanini et al, 1998;Greatens et al, 1998;D'Amico et al, 1999;Fu et al, 1999;Cox et al, 2000;Ohsaki et al, 2000;Selvaggi et al, 2002;Hirsch et al, 2003;Kanematsu et al, 2003;Mukohara et al, 2003;Onn et al, 2003). The majority of these studies have failed to demonstrate an association with prognosis (Table 1).…”
mentioning
confidence: 99%